FILSAFAT PENDIDIKAN TERHADAP POLA PIKIR DAN PERILAKU SOSIAL MAHASISWA - Muh Nur; Saripuddin; Fatimah Aziz; Kaharuddin (STKIP Subang, 2025)
Every individual is connected to philosophy in the learning process. Individuals need to be able to think philosophically in the field of education. Philosophy is generally focused on students so they can understand the nature and responsibility of their thinking. Therefore, the purpose of this study is to determine the role of educational philosophy on students' mindsets and social behavior. This study applies a qualitative method with a literature study approach. The results show that educational philosophy has enormous potential to improve the quality of critical and creative thinking in students. Educational philosophy also plays a crucial role in shaping students' social awareness. The application of ethics creates a constructive learning atmosphere, respects diversity, and encourages students to be responsible, empathetic, and have integrity. Keyword: Philosophy of Education, Mindset, Social Behavior, Students